YIA 03-10 ENDOTHELIAL KRUPPEL-LIKE FACTOR 15: A NOVEL TARGET FOR THE TREATMENT OF PULMONARY HYPERTENSION. (September 2016) - Pandey, Deepesh; Tori, Daijiro; Nomura, Yohei; Berkowitz, Dan; Romer, Lewis
Abstract : Objective: Kruppel Like Factor 15 (KLF15) has recently been shown to be critical for activation of proinflammatory processes in vascular smooth muscle and atherogenesis. Although KLF15 is abundantly expressed in vascular endothelium there is a significant lack of knowledge regarding the role of KLF15 in the regulation of vascular endothelial function. Here we tested the hypothesis that KLF15 is a critical regulator of Arg2 transcription in hypoxia exposed human pulmonary microvascular endothelial cells (HPMEC) and that it plays critical role in pathogenesis of pulmonary hypertension (PHTN). Design and Method: Overexpression and Knockdown of KLF15 in HPMEC was acheived by transducing cells by adenoviruses encoding KLF15 cDNA and shRNA respectively. Pulmonary endothelial dysfunction was assessed by determining a. Nitric Oxide release by Siever's NO analyzer, b. superoxide production by luminol based chemiluminescence and c. acetylcholine dependent pulmonary artery relaxation measured by wire-myography. Interaction between Arg2 promoter and KLF15 was determined by Chromatin immunoprecipitation. Results: Increased expression of KLF15 in human pulmonary microvascular endothelial cells (HPMEC) and in rat pulmonary arteries decreased Arg2 mRNA, protein, and activity. HPMECs exposed to 48 hours of hypoxia, a potent stimulus for PHTN, exhibited a robust increase in Arg2 protein and mRNA expression and a reciprocal decrease in KLF15 protein levels that remain sustained after 24 hours of reoxygenation. ChIP assay indicated direct binding of KLF15 to the Arg2 promoter, which was relieved when HPMEC were exposed to hypoxia, Finally, overexpression of KLF15 reversed hypoxia-induced augmentation of arginase activity and decrements in Nitric Oxide production in HPMEC, and also reversed hypoxia-induced endothelial dysfunction in isolated rat pulmonary artery rings. Conclusions: KLF15 is a critical regulator and repressor of endothelial Arg2 expression, and thereby, NO and pulmonary endothelial function. Overexpression or activation of KLF15 may represent novel therapeutic strategies for pulmonary hypertension.